Application of multi-omics technology in pathogen identification and resistance gene screening of sheep pneumonia - Kai Huang; Lvfeng Yuan; Jia Liu; Xiaolong Li; Dan Xu; Xiaoxue Zhang; Jie Peng; Huibin Tian; Fadi Li; Weimin Wang (BMC Genomics)
Abstract Background Pneumonia constitutes a major health challenge in sheep, severely compromising growth rates and overall productivity, and resulting in considerable economic losses to the sheep industry. To address this issue, the development of disease-resistant breeding programs based on the identification of genetic markers associated with pneumonia susceptibility is of critical importance. This study investigated a sheep population on a farm where pneumonia was endemic. The purpose was to use multi-omics methods to rapidly identify the principal pathogens responsible for pneumonia outbreaks, and to screen for genetic loci and key genes related to pneumonia resistance, thereby providing a scientific basis for the implementation of targeted breeding strategies for pneumonia resistance. Results Here, we assessed the impact of pneumonia on sheep growth by evaluating the pneumonia phenotypes of 912 sheep. High-throughput transcriptome sequencing of 40 lungs was conducted to obtain exogenous RNA fragments for microbial sequence alignment. Additionally, 16S rRNA sequencing was performed on lung tissues from 10 healthy and 10 diseased sheep to identify biomarkers associated with phenotypic differences. Mycoplasma ovipneumoniae was identified as the primary pneumonia pathogen, and its presence was further validated by load quantification and immunohistochemical analysis. Integration of genome-wide association study (GWAS) data from 266 lung pathological scores with transcriptome-based differentially expressed genes analysis enabled the identification of five single nucleotide polymorphisms (SNPs) and three potential candidate genes associated with Mycoplasma pneumonia. Subsequent genotyping and phenotype association analyses confirmed the significance of two SNPs and established a strong association between the FOXF1 gene and resistance to Mycoplasma pneumonia. Conclusions High-throughput sequencing technologies have enabled the rapid and accurate identification of the causative pathogen of sheep pneumonia. By integrating multi-omics data, two genomic loci significantly associated with Mycoplasma pneumonia were screened, as well as an anti-Mycoplasma pneumonia key gene, FOXF1.